Review of Neuro‑nutrition Used as Anti‑Alzheimer Plant, Spinach, Spinacia oleracea - Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Neuro‑nutrition is the nutrition needed to achieve health brain and neurocognitive function. Diets rich in antioxidants, vitamins, flavonoids, and polyphenolic compounds will help suppress the onset of Alzheimer’s disease. Spinacia oleracea (Family: Amaranthaceae) commonly known as spinach or Buai Leng (in Thai), one of the traditional medicinal plants with high in those mention nutrients. The micronutrients in spinach include a range of vitamins and minerals, which can prevent deficiency diseases and are essential for normal physiological function. Its phytochemicals are carotenoids, flavonoids, and phenolic compounds, which can prevent chronic health problems, as well as other diseases associated with aging. The objective of this article was to conduct a review on various ethnomedicinal uses of the spinach and its influences on the pathophysiology of Alzheimer’s disease based on a literature review.
Keywords: Alzheimer; herb; neuro‑nutrition; plant; spinach; Spinacia oleracea